Unveiling the immunomodulatory dance: endothelial cells’ function and their role in non-small cell lung cancer - Sophia Daum; Lilith Decristoforo; Mira Mousa; Stefan Salcher; Christina Plattner; Baharak Hosseinkhani; Zlatko Trajanoski; Dominik Wolf; Peter Carmeliet; Andreas Pircher (Molecular Cancer)
Abstract The dynamic interactions between tumor endothelial cells (TECs) and the immune microenvironment play a critical role in the progression of non-small cell lung cancer (NSCLC). In general, endothelial cells exhibit diverse immunomodulatory properties, influencing immune cell recruitment, antigen presentation, and regulation of immune checkpoint expression. Understanding the multifaceted roles of TECs as well as assigning specific functional hallmarks to various TEC phenotypes offer new avenues for targeted development of therapeutic interventions, particularly in the context of advanced immunotherapy and anti-angiogenic treatments. This review provides insights into the complex interplay between TECs and the immune system in NSCLC including discussion of potential optimized therapeutic opportunities.